Paula Danziger's Amber Brown is tickled pink - Coville, Bruce; Levy, Elizabeth, 1942-; Ross, Tony; Danziger, Paula, 1944-2004. (New York : G.P. Putnam's Sons, 2013)
Nine-year-old Amber is nervous and excited about her mother's wedding to Max, but Amber's father makes things complicated.
Keywords: Remarriage -- Fiction; Weddings -- Fiction